HUBUNGAN SAFETY CULTURE DENGAN PERILAKU KESEHATAN DAN KESELAMATAN KERJA PADA PUSAT TEKNOLOGI DAN KESELAMATAN REAKTOR NUKLIR BATAN TAHUN 2020 - Mairing, Carolyna; Wirawan, I Made Ady; Deswandri, Deswandri (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 1 (2021): April 2021DO - 10.24843/ACH.2021.v08.i01.p05, 2021)
ABSTRACT Safety culture is an organizational culture that prioritizes safety values and attitudes. Although the company has called on workers to prioritize safety, workers do not yet understand that safety behavior for workers is important to avoid both occupational illness and work accident. This study aims to determine the relationship between safety culture and individual factors with safety behavior at the Nuclear Reactor Technology and Safety Center BATAN. This study uses quantitative analytic research with a cross-sectional study design. Respondents in this study amounted to 51 people with a purposive sampling technique. The results show the proportion of respondents have nice safety behavior at 49.02%. A higher level of education has     a significantly higher proportion of safety behavior (p = 0.023), while the age, sex, years of service and safety culture variables are not significantly related to safety behavior (p> 0.05). Therefore it is necessary to look at the wider factors that influence safety behavior. Besides, improvement of occupational health and safety should be targeted. Keywords: Safety culture, Safety behavior, Workers